The impact of acute kidney failure in patients hospitalized for COVID-19 (Research, Society and Development, 2022)
Introduction: Acute renal failure (ARI) is a sudden reduction in kidney function with various phenotypes and represents one of the complications of infection with the new coronavirus. There is a multifactorial association between these entities, affecting the severity of the patients' health condition. Objective: The objective of this article is to search the literature for evidence of acute kidney injury among those hospitalized with COVID-19 and describe aspects of the phenomenology of this injury in this situation. Methodology: Systemic review of the literature in the databases, PubMed, productions carried out in the last 2 years. The descriptors used were: "IRA", "COVID-19", "SARS-CoV-2", in conjunction to define the search. Results: At the end of the stages, 15 articles were selected, 9 from 2020, corresponding to 60% and 6 from 2021, 40%. All these studies are observational. ARI is a frequent finding and may be caused by viral progression. There are previous factors that predict higher risk, such as systemic arterial hypertension, diabetes mellitus, and chronic obstructive pulmonary disease. Knowing this, screening and monitoring of renal function since admission is extremely important to identify initial changes that can be controlled or reversed, as it increases the risk of mortality and the use of corticosteroids apparently helps to reduce this risk. Plasmapheresis and renal replacement therapies should be considered. Final Considerations: Therefore, the evidence is that the development of ARI in these cases is related to higher mortality, morbidities and treatment therapies after discharge. Factors such as age, obesity and genetics favor AKI in these patients, generating negative repercussions on the prognosis.